HUBUNGAN STATUS MUTU AIR METODE INDEKS PENCEMARAN DENGAN KEGIATAN KERAMBA JARING APUNG DI WADUK RIAM KANAN KECAMATAN ARANIO KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Nida Nida; Mijani Rahman; Abdur Rahman (Fish Scientiae, 2017)
This study aims to determine the status of water quality in the Riam Kanan Reservoir seen from the physical parameters (Temperature and Brightness) and chemical parameters (pH, DO, Total Phosphate, Nitrate and Ammonia) using Pollution Index (IP) method, knowing trophic level in Riam Kanan reservoir seen from the parameter of Brightness, Total Phosphate and Total Nitrogen and know the influence of floating net cage activity to water quality status of Riam Kanan reservoir. Of the result on measurement of IP method water quality which based on the, the status of water quality in station 1, 2, and 3 was complied with water quality standard (goodcondition), either for class I, II, III, or IV. Based on the regulation of the state minister for environment Number 28 Year 2009 was found that the fertility level in station 1, 2, and 3 wasin the same trophic status, which was oligotrophic. The value of thit nitrate (X1), total P (X2)and ammonia (X3) either for class I, II, III, or IV was lower than t tabel for significance in 5% orsig/.probability > 0,05 which meant that H0 was accepted; KJA activities did not affect the water quality status of Riam Kanan dam.